2014
DOI: 10.1016/j.amjsurg.2013.09.024
|View full text |Cite
|
Sign up to set email alerts
|

Acute phase proteins in drain fluid: a new screening tool for colorectal anastomotic leakage? The APPEAL study: analysis of parameters predictive for evident anastomotic leakage

Abstract: BACKGROUND: We aim to determine if C-reactive protein (CRP), lipopolysaccharide-binding protein (LBP), and procalcitonin (PCT) in drain fluid can serve as screening tools for colorectal anastomotic leakage (CAL).METHODS: Patients included in this multicenter prospective observational study underwent left hemicolectomy, sigmoid resection, high anterior resection, low anterior resection, or subtotal colectomy. During the first 5 postoperative days, CRP, LBP, and PCT were determined on drain fluid. RESULTS: In to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
32
0
8

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 40 publications
(42 citation statements)
references
References 38 publications
2
32
0
8
Order By: Relevance
“…Similar conclusions had been got in other researches [7,10,14,18]. There are also studies to determine whether PCT in drain fluid can serve as screening tool for AL [19]. Unfortunately, the results showed that examination of PCT in drain fluid could not help to detect AL.…”
Section: Procalcitoninsupporting
confidence: 66%
See 4 more Smart Citations
“…Similar conclusions had been got in other researches [7,10,14,18]. There are also studies to determine whether PCT in drain fluid can serve as screening tool for AL [19]. Unfortunately, the results showed that examination of PCT in drain fluid could not help to detect AL.…”
Section: Procalcitoninsupporting
confidence: 66%
“…The details were summarized in Table 1, Table 2, and Table 3. There are also studies to determine whether CRP in drain fluid can serve as screening tool for AL [18,19]. However, the results showed that examination CRP in drain fluid could not help to detect AL.…”
Section: C-reactive Proteinmentioning
confidence: 88%
See 3 more Smart Citations